2012
DOI: 10.1007/s00438-012-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Siah-interacting protein gene in Drosophila causes cardiomyopathy

Abstract: Drosophila is a useful model organism in which to study the genetics of human diseases, including recent advances in identification of the genetics of heart development and disease in the fly. To identify novel genes that cause cardiomyopathy, we performed a deficiency screen in adult Drosophila. Using optical coherence tomography to phenotype cardiac function in awake adult Drosophila, we identified Df(1)Exel6240 as having cardiomyopathy. Using a number of strategies including customized smaller deletions, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…57 Recent work showed that while β-CAT overexpression has no measurable effects, its knockdown induces significant dysfunction. 58 While β-CAT could have a role in pathological disease, we have recently demonstrated that its counterpart–α-catenin–was upregulated in aged, non-diseased simian and fly hearts using proteomic and genetic analyses. Data suggest that α-CAT appears upregulated with physiological aging 51 and may precede pathological remodeling (Figure 1, red).…”
Section: Intracellular Remodeling As a Results Of Stress Age Or Diseasementioning
confidence: 99%
“…57 Recent work showed that while β-CAT overexpression has no measurable effects, its knockdown induces significant dysfunction. 58 While β-CAT could have a role in pathological disease, we have recently demonstrated that its counterpart–α-catenin–was upregulated in aged, non-diseased simian and fly hearts using proteomic and genetic analyses. Data suggest that α-CAT appears upregulated with physiological aging 51 and may precede pathological remodeling (Figure 1, red).…”
Section: Intracellular Remodeling As a Results Of Stress Age Or Diseasementioning
confidence: 99%
“…While we do not have a definitive reason to explain how reduction of a gene with low RNA expression results in an observable phenotype, we note that other important developmental genes show the same pattern. For example, expression of Pan is low in S2 cells and during development ( Graveley et al 2011 ) and yet its reduction leads to heart development defects ( Casad et al 2012 ). Collectively, the results presented here indicate that methionine metabolism and histone methylation are critical for Drosophila development.…”
Section: Discussionmentioning
confidence: 99%